Applying advanced technologies for enhancing construction safety management: the contractor's perspective - Chung, Seow Ling (2024)
The construction sector is progressively integrating advanced technologies to augment safety management and optimise project efficiency. Technologies including Exoskeleton, Artificial Intelligence (AI), Sensing Technology, UAVs and drones, 3D-Printing, Building Information Modelling (BIM), Modular Construction, Internet of Thing (IoT) and YOLOv3 are instrumental in mitigating safety hazards, enhancing collaboration, and optimising construction processes. Notwithstanding these developments, numerous organisations encounter substantial obstacles, especially the elevated expenses connected with the adoption and maintenance of these technologies. Furthermore, these advanced technologies ineffectively combine with existing safety management systems as well as the gap in the construction workforce's digital literacy prevents the full utilization of these advanced technologies. This study identified the advanced technologies for managing construction safety, explores the essential of advanced technologies in managing construction safety, and evaluates the barriers of advanced technology adoption in managing construction safety. 166 responses were received for this study. The survey data analysis indicated that BIM, drones, and AI are the three most recognised and extensively utilised technology among respondents. The study ascertained that personal exposure and experience as determinant of familiarity and essential to adoption of advanced technologies. The study identified financial restrictions as the primary obstacle to adoption. Moreover, company size and CIDB grade significantly influenced perceptions of these barriers, beyond the effects of working experience or position, as larger companies and those with higher CIDB grades were more inclined to surmount these challenges. This study offered contributions to various stakeholders including policymakers and government, industry, universities and academic institutions as well as upcoming researchers to grow in their own aspects. In conclusion, although advanced technologies are becoming common, financial and logistical restrictions persist as significant obstacles.